Prosperity Gospel: To Save or to Enslave? The Case of United Family International (UFI) in Zimbabwe - Masvotore, Peter (University of Zimbabwe, 2012)
This book is a contemporary study of prosperity gospel. It investigates whether it saves or enslaves. The contents of the book investigates the reasons for the emergence of the gospel of prosperity as propounded by UFI and its applicability in times of economic crisis. The motivation of this book comes as a challenge to the Church in Zimbabwe where it grapples with the challenge posed by this gospel among its flock. One cannot speak about theology and the church without looking at its role in addressing social, spiritual and political realities in society. This gospel arose in the time of economic crisis in Zimbabwe; hence one is prompted to find out if it is a survival strategy in churches, or a form of empowerment. It traces the roots and emergence of the gospel of prosperity and the history of UFI and explores some biblical interpretations by advocates of prosperity gospel in UFI. It also evaluates the theological implications of this gospel and provides an analysis, conclusion and way forward.The book deduced some advantages gained through propagating this gospel.Some theological problems posed by this gospel were noted. It provokes churches to think out of the box.
free